Transient dynamic balancing of the rotor system with uncertainty. (15th May 2022) - Zhao, Shibo; Ren, Xingmin; Zheng, Qingyang; Lu, Kuan; Fu, Chao; Yang, Yongfeng
Highlights: The transient dynamic balancing of the uncertain rotor dynamic is analyzed. The uncertainty quantification and transient balancing methods are first combined. Uncertainties are described by multi-dimensional ellipsoid model. Uncertainties are quantified by Monte Carlo Simulation and Chebyshev interval algorithm. The transient balancing method succeeds in balancing without trail weights during acceleration. Abstract: The non-intrusive uncertainty quantification methods and the transient dynamic balancing method are proposed in this paper, which are combined for the first time to analyze the transient dynamic balancing of the rotor system with uncertainty. Uncertainties are described by multi-dimensional ellipsoid model (MEM) and quantified as the transient uncertain responses obtained by Monte Carlo Simulation (MCS) and Chebyshev interval algorithm (CIA), respectively. The transient dynamic balancing method is supposed to balance the rotor system by the transient uncertain responses and the variable system modal characteristics due to the uncertain parameters during acceleration. The simulation analysis and experimental tests of the single disc rotor system are carried out. The results show that the proposed uncertainty quantification methods can keep good accuracy in vibration prediction of the accelerating transient process. And the maximum deflection decrease range of the disc is 68.20–72.32% in experimental tests, verifies the effectiveness and reliability of the proposed balancing method in balancing the rotor system with uncertainty. The transient dynamic balancing of the uncertain rotor system will facilitate the on-site dynamic balancing process and will definitely improve reliability and safety of the rotor system during operation at high speed.